Podocoryna martinicana, a new species of athecate hydroid (Cnidaria: Hydrozoa: Hydractiniidae) from the Caribbean - Galea, Horia R.; Ferry, Romain (Zootaxa, 2013)
A new species of hydroid, Podocoryna martinicana sp. nov., is described from the Lesser Antilles. It lives symbiotically with Iridopagurus caribbensis (A. Milne-Edwards & Bouvier, 1893) (Decapoda: Paguridae) inhabiting various gastropod shells. Its colonies are highly organized and develop exclusively around the aperture of the host shell. A few large, columnar gastrozooids provided with numerous tentacles arise from a perisarc-covered stolonal mat on the inner lip of the shell, and appear to form a gate when the hermit is withdrawn, while numerous, small, highly prolific gonozooids dress a line on the edge of the outer lip. Slender, very contractile tentaculozooids occur variably among the colonies. The dispersive stage, a free-swimming medusa with four well-developed marginal tentacles and no ocelli, is solely described based on young, sexually immature specimens. The species is further characterized by the peculiar bright white tinge of the core of both hydroid and medusa tentacles. Rich illustrations, data on the nematocyst complement, as well as comparisons with related congeners are provided.